Assessing emergency regulation technology in the Middle Route of the South-to-North Water Diversion Project, China. Issue 3 (4th May 2018) - Lei, Xiaohui; Zheng, Hezhen; Shang, Yizi; Wang, Hao
Abstract: The Middle Route of the South-to-North Water Diversion Project is important for China. Any sudden water pollution accident along the route would threaten normal water supply. We studied four technologies (hydrodynamic and water quality simulation, source identification, emergency regulation, and evaluation of emergency measures) and developed and implemented a decision support system that provides technical support in managing pollution accidents. The achievements, which include four technologies and a system, have practical significance for emergency management in the Middle Route as they can help deal with accidents and policy formulation, and can be applied to other water transfer projects.